From Literacy to Loyalty: How Big Five Personality Traits Influence Taxpayer Compliance - Yusnaini Yusnaini; Raka Bagus Prakoso (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
The research aims to examine the effect of tax literacy on individual taxpayer compliance, with particular attention to the moderating role of the Big Five personality traits: extraversion, conscientiousness, openness, neuroticism, and agreeableness. This study is motivated by the persistently low level of tax compliance in Indonesia, despite the government’s extensive efforts in taxpayer education and system reform. A quantitative research method was employed, using a survey approach with questionnaires distributed to individual taxpayers who possess a taxpayer identification number (TIN) and regularly file their tax returns. The sampling technique applied was accidental sampling, yielding a total of 300 Muslim respondents. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA), with the assistance of Stata version 17 software. The results reveal that tax literacy has a positive and significant effect on taxpayer compliance. Furthermore, the traits of extraversion, conscientiousness, and agreeableness significantly moderate the relationship between tax literacy and tax compliance, while openness and neuroticism do not exhibit significant moderating effects. These findings carry important implications for tax authorities, suggesting that efforts to improve compliance should not only focus on enhancing tax literacy but also consider personality characteristics in designing more effective compliance strategies.